The operational space for divertor power exhaust in DEMO with a super-X divertor. (31st May 2021) - Xiang, L.; Militello, F.; Moulton, D.; Subba, F.; Aho-Mantila, L.; Coster, D.; Wensing, M.; Lunt, T.; Wischmeier, M.; Reimerdes, H.
Abstract: SOLPS-ITER simulations of the European DEMO reactor with a Super-X divertor, which has larger major radius at the outer target and increased connection length, show an increased operational space for divertor power exhaust compared to the conventional single-null configuration. Using a multi-fluid approach with fluid neutrals and charge-state bundling of impurities, we assessed the existence and boundaries of the operational space in the single-null and Super-X configurations by carrying out fuelling, seeding and power scans. Compared to the conventional single-null divertor, the Super-X divertor offers lower impurity concentration (factor ∼2 lower) at the same main plasma density, and consistent with this, it has lower main plasma density at the same impurity concentration level. This observed difference is in line with the simple analytical Lengyel model predictions resulting from the increased connection length in the super-X configuration. DEMO with a Super-X divertor demonstrates remarkable robustness against increases in input power, and in this study is able to exhaust the maximum expected steady-state separatrix-crossing power of 300 MW while maintaining acceptable impurity concentration along the separatrix This is something that was not possible in the single-null configuration in this study. This robustness of the Super-X divertor lies mostly in its capability to sufficiently dissipate power in its divertor via argon (Ar) radiation at acceptable Ar concentration, which is related to two factors: long (with respect to single-null) parallel connection length from the upstream to the outer target and higher but tolerable extrinsic impurity concentration at higher input powers. Finally, consistent with neon-seeded simulations of ITER, it is observed in all our simulations that the plasma density drops with increasing Ar concentration given fixed power input. We find that as the Ar content increases, the accompanying enhancement of Ar radiation reduces the power available for deuterium (D) to be ionized, thus limiting the D ionization particle source, and consequently reducing the plasma density.